بنية الشخصية والحدث في رواية "نزوح مريم" للمحمود حسن الجاسم: The structure of character and event in the novel “Maryam’s Exodus” by Maḥmūd Ḥasan al-Jāsim - Naz, Dr. Robina (Al-Amīr Research Journal for Islamic Studies, 2024)
The novel is one of the literary genres that is concerned with social issues, reflects the image of reality in an artistic and aesthetic way, and addresses many psychological and social problems. The writer may resort to it to convey his thoughts, feelings, emotions, and experiences to the recipient. The character is one of the most prominent elements of the novel and is considered the center of the novel’s work. Through its interaction, the features of the novel are shaped and the events are formed. It is a figment of the writer’s imagination. He transmits life into it and depicts it in an accurate artistic manner. It is the focus of the writer’s thoughts and feelings, and helps him understand the events and depict them. Maḥmūd Ḥasan al-Jāsim embodied the painful reality in his novel Maryam’s Exodus, which leaves a profound impact on readers. This study attempts to shed light on the construction of character and event in the novel Maryam’s Exodus, as it presents a depiction of Syrian society with all its political, social, religious and cultural spectrums. Characters interact with events, and events with characters in their formation and construction. This research deals with both of them together to reveal their features, and highlight the way they are presented, their types, functions, and their relationship with the rest of the other narrative components. The study consists of introduction, the two sections, and the conclusion. The introduction includes the importance of the topic, while the first section includes the concept of characters, their types, and their dimensions in the novel, and the second section deals with the concept of the event and its types in the novel. The conclusion includes the most important results reached. Keywords: Novel, Structure, Character, Event, Maryam’s Exodus, Maḥmūd Ḥasan al-Jāsim